2007
DOI: 10.1016/j.bbmt.2007.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival after Autologous Bone Marrow Transplantation for Follicular Lymphoma in First Remission

Abstract: The role of autologous stem cell transplantation (ASCT) in the treatment of follicular lymphoma is still being defined in the era of antibody therapy. Here we report the long-term 12-year clinical outcomes of patients treated with autologous bone marrow transplantation (ABMT) for follicular non-Hodgkin's lymphoma (NHL) in first remission. Between 1988 and 1993, advanced-stage follicular NHL patients in need of initial therapy were enrolled in 2 consecutive prospective treatment trials of either standard-dose C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…16,[35][36][37] However, significant toxicities can be associated with global lymphodepletion-conditioning regimens and autologous stem cell transplantation. [38][39][40][41] Our results show that B-cell depletion alone, which produces few toxicities in patients, 42 is sufficient to allow T cells to eliminate a modest established leukemia burden without producing long-term T cell-mediated B-cell lymphopenia. In contrast to global lymphodepletion, 35 B-cell depletion did not induce homeostatic proliferation of T cells, but it did promote modest antigen-specific proliferation that may contribute to the antileukemic response.…”
Section: Discussionmentioning
confidence: 70%
“…16,[35][36][37] However, significant toxicities can be associated with global lymphodepletion-conditioning regimens and autologous stem cell transplantation. [38][39][40][41] Our results show that B-cell depletion alone, which produces few toxicities in patients, 42 is sufficient to allow T cells to eliminate a modest established leukemia burden without producing long-term T cell-mediated B-cell lymphopenia. In contrast to global lymphodepletion, 35 B-cell depletion did not induce homeostatic proliferation of T cells, but it did promote modest antigen-specific proliferation that may contribute to the antileukemic response.…”
Section: Discussionmentioning
confidence: 70%
“…Most studies showed that MRD negativity is associated with a superior outcome and acts as an independent predictor. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] However, a few studies failed to confirm this observation. [25][26][27][28] In particular, a recent report by van Oers et al 28 failed to demonstrate any benefit of achieving postinduction PCRnegative status.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The risk for recurrence is more pronounced among patients older than 60 years, as they often receive less-intense treatments. 4 Considerable evidence indicates that the persistence of polymerase chain reaction (PCR)-detectable residual tumor cells in the bone marrow (BM) and, to a lesser extent, peripheral blood is an independent predictor of relapse in FL [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] ; nevertheless, a few studies have failed to confirm this observation. [25][26][27][28] Concerns about the value of minimal residual disease (MRD) detection as an effective prognostic tool have been raised, particularly when applied to The results of this study were the subject of an oral presentation at the 2012 American Society of Hematology annual meeting.…”
Section: Introductionmentioning
confidence: 99%
“…65 An institutional review from the Dana-Farber Cancer Institute with a 12-year follow-up of patients undergoing ASCT as consolidation of primary therapy reported a second malignancy incidence of 28%. 66 In these 27 patients, the malignancies included 10 cases of therapy-related myelodysplastic syndrome (T-MDS) or therapy-related acute myeloid leukemia (T-AML), 2 other hematologic malignancies, 9 solid tumors, and 10 nonmelanoma skin cancers. The cumulative incidence of second malignancy in a competing risk model was estimated to be 38% at 15 years.…”
Section: Secondary Malignancies After Sctmentioning
confidence: 99%